CADASIL-A RARE PRESENTATION OF STROKE - DAMA, AASHISH; JAIN, PULKIT; SINGH, JITENDRA; SALVE, CHANDRA KANT; SHARMA, ASHISH (International Journal of Current Pharmaceutical Research, 2024)
Objective: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a hereditary syndrome caused by heterozygous mutations in the NOTCH3 gene that manifests in adulthood and is characterized by recurrent transient ischemic attacks and strokes, migraine-like headaches, psychiatric disturbance, and progressive dementia. Methods: This is a case report. Results: Current case presented with complain of dizziness and vomiting. The diagnosis was suspected mainly because of the typical brain magnetic resonance imaging (MRI). This shows the importance of brain MRI in the diagnosis of CADASIL. Conclusion: Increased awareness of neurologists and neuroradiologists about the typical MRI features of CADASIL is of vital importance to reach the diagnosis in a timely manner.